Ca. 850 Ma Bimodal Volcanic Rocks in Northeastern Jiangxi Province, South China: Initial Extension During the Breakup of Rodinia? - Li, W.; Li, X.; Li, Zheng-Xiang (American Journal of Science, 2010)
Multiple Meso- to Neoproterozoic magmatic events in South China are believed to record the transition in tectonic regime from the assembly of the supercontinent Rodinia to its breakup. We document in this paper the earliest, ca. 850 Ma bimodal volcanism in South China which may indicate the beginning of continental extension and rifting. The Zhenzhushan bimodal volcanic rocks were dated at 849 ± 6 Ma using the secondary ion mass spectrometry (SIMS) U-Pb zircon method. The mafic members of the succession are Si-saturated tholeiitic basalts with moderate enrichment in most incompatible trace elements and high Nd(T) values of 2.1 to 4.8. This suggests a likely derivation of the basalts from a depleted asthenospheric mantle source in an extensional environment, and that the magma experienced low-degree fractional crystallization and crustal contamination during its ascent to the surface.The felsic members are peraluminous and are characterized by negative Nd(T) values of –0.3 to –1.9 with geochemical features similar to those of the adjacent ca. 820 Ma peraluminous granitoids derived from a Mesoproterozoic to earliest Neoproterozoic sedimentary source. In combination with the distribution of 850 to 830 Ma igneous and sedimentary successions in South China, we suggest that continental rifting along the southern margin of the Yangtze Block probably started by 850 Ma. Coeval anorogenic magmatism has also been reported in other parts of the Rodinia supercontinent, and may represent the early stage of the Rodinia superplume in response to a circum-Rodinia mantle avalanche after the complete assembly of the supercontinent.